Recent Topics of Organic Superconductors - Ardavan, A; Brown, S; Kagoshima, S; Kanoda, K; Kuroki, K; Mori, H; Ogata, M; Uji, S; Wosnitza, J (2012)
Recent developments in research into superconductivity in organic materials are reviewed. In the epoch-defining quasi-one-dimensional TMTSF superconductors with T c ∼ 1 K, T c decreases monotonically with increasing pressure, as do signatures of spin fluctuations in the normal state, providing good evidence for magnetically-mediated pairing. Upper critical fields exceed the Zeeman-limiting field by several times, suggesting triplet pairing or a transition to an inhomogeneous superconducting state at high magnetic fields, while triplet pairing is ruled out at low fields by NMR Knight-shift measurements. Evidence for a spatially inhomogeneous superconducting state, Fulde-Ferrel-Larkin- Ovchinnikov state, which has long been sought in various superconducting systems, is now captured by thermodynamic and transport measurements for clean and highly two-dimensional BEDT-TTF and BETS superconductors. Some of the layered superconductors also serve as model systems for Mott physics on anisotropic triangular lattice. For example, the Nernst effect and the pseudo-gap behavior in NMR relaxation are enhanced near to the Mott transition. In the case of increasing spin frustration, the superconducting transition temperature is depressed, and antiferromagnetic ordering is eliminated altogether in the adjacent Mott insulating phase. There is an increasing number of materials exhibiting superconductivity in competition or cooperation with charge order. Theoretical studies shed light on the role of spin and/or charge fluctuations for superconductivity appearing under conditions close to those of correlation-induced insulating phases in the diversity of organic materials. © 2012 The Physical Society of Japan.